Linking Empowering Leadership to Task Performance, Taking Charge, and Voice: The Mediating Role of Feedback-Seeking - Qian, Jing; Song, Baihe; Jin, Zhuyun; Wang, Bin; Chen, Hao (Frontiers in Psychology, 2018)
Drawing upon the person-environment fit theory, the present study focuses on the role of feedback-seeking in linking empowering leadership to task performance, taking charge, and voice. We tested the hypothesized model using data from a sample of 197 supervisor-subordinate dyads. Performing powerful methods of analysis (e.g., CFA, SEM, and bootstrapping), the results revealed that: (1) empowering leadership was positively associated with followers’ feedback-seeking; (2) employees’ feedback-seeking was positively correlated with task performance, taking charge, and voice; and (3) employees’ feedback-seeking mediated the positive relationships between empowering leadership and task performance, taking charge, and voice. We make conclusions by discussing the theoretical and practical implications of these findings, alongside a discussion of the present limitations and directions for future studies.